Factors associated with nutritional deficiency biomarkers in candidates for bariatric surgery: A cross-sectional study in a peruvian high-resolution clinic - Riva-Moscoso, Adrian (2022)
Previous studies have described multiple nutritional deficiencies after bariatric surgery (BS). However, few studies have evaluated these deficiencies prior to BS, specifically in Latin America. This study aimed to determine the factors associated with nutritional deficiency biomarkers in candidates for BS in Peru. We included adults of both sexes, aged 18 to 59 years, admitted to a Peruvian clinic with a body mass index (BMI) ≥ 30 kg/m2; they were candidates for BS from 2017 to 2020. We considered the serum levels of hemoglobin and albumin (in tertiles) as the nutritional deficiency biomarkers. In order to assess the associated factors, we calculated crude (cPR) and adjusted prevalence ratios (aPR) with their respective 95% confidence intervals (95%CI). We analyzed 255 patients: 63.1% were males, with a mean age of 37.1 ± 10.3 years and mean hemoglobin and albumin values of 14.0 ± 1.5 g/dL and 4.6 ± 0.4 g/dL, respectively. We found that males (aPR = 1.86; 95%CI: 1.26–2.73; p = 0.002), participants between 30 and 49 (aPR = 2.02; 95%CI: 1.24–3.28; p = 0.004) or 50 years or more (aPR = 2.42; 95%CI: 1.35–4.35; p = 0.003), participants with a BMI ≥40 kg/m2 (aPR = 1.68; 95%CI: 1.09–2.60; p = 0.018), participants with impaired high-density lipoprotein levels (aPR = 1.43; 95%CI: 1.01–2.05; p = 0.049) and individuals in the high tertile of C-reactive protein (aPR = 6.94; 95%CI: 3.37–14.32; p < 0.003) had a higher probability of being in the lower tertile of albumin. In addition, we found that the male sex (aPR = 6.94; 95%CI: 3.37–14.32; p < 0.001) and elevated cholesterol levels (aPR = 0.71; 95%CI: 0.52–0.97; p = 0.034) were associated with the lowest hemoglobin tertile. In our setting, nutritional deficiency biomarkers were associated with sociodemographic, anthropometric and laboratory markers. The pre-bariatric surgery correction of nutritional deficiencies is essential, and can prevent major complications after surgery.